Cohabitation of Piscirickettsia salmonis genogroups (LF-89 and EM-90): synergistic effect on growth dynamics - Carril, Gabriela; Winther-Larsen, Hanne C.; Løvoll, Marie; Sørum, Henning (Frontiers in Cellular and Infection Microbiology, 2023)
Piscirickettsia salmonis, the biological agent of Salmonid Rickettsial Septicemia (SRS), is a facultative intracellular bacterium that can be divided into two genogroups (LF-89 and EM-90) with different virulence levels and patterns. Studies have found co-infection of these genogroups in salmonid farms in Chile, but it is essential to assess whether this interaction within the host is related to virulence and changes in pathogen dynamics. In this study, we studied four isolates from EM-90 and one LF-89 isolate chosen based on their genomic differences. The aim was to evaluate how co-cultivation affects bacterial growth performance and virulence factor expression in Atlantic salmon (Salmo salar) in vitro and in vivo. In vitro results using FN2 medium, showed a similar growth curve between co-cultures of LF-89 and EM-90 compared to EM-90 monocultures. This was explained by the higher ratio of EM-90 to LF-89 in all co-cultures. When evaluating the expression of virulence factors, it was discovered that the luxR gene was expressed only in EM-90-like isolates and that there were significant differences between mono- and co-cultures for flaA and cheA, suggesting a response to cohabitation. Moreover, during in vivo co-cultures, transcriptomic analysis revealed an upregulation of transposases, flagellum-related genes (fliI and flgK), transporters, and permeases that could unveil novel virulence effectors used in the early infection process of P. salmonis. Thus, our work has shown that cohabitation of P. salmonis genogroups can modulate their behavior and virulence effector expression. These data can contribute to new strategies and approaches to improve the current health treatments against this salmonid pathogen.